Lei de drogas: etnografando o encarceramento da mulher na prisão feminina Maria Júlia Maranhão (João Pessoa-PB) - Ferreira, Núbia Guedes de Barros (2022)
The objective of the present work is to ethnography a fear of a child: “fear of not having anyone else for us”. In this sense, this study aims to understand the incarceration of women and their relationships around matrifocality under the fulcrum of the Drug Law. In a basic way, the research consists of an ethnography carried out with women imprisoned in a closed regime and with their families on the day of the visit. The Drug Law, nº 11.343/2006, is the main incursion of women found in Brazilian prisons. The research points to the law referred to as a rationality of the State, the biopolitics for the social control of bodies, a social hygiene of colonialist and racist ballast. In the field, different ways of perceiving women's immersion in drug trafficking are revealed. From “easy profit” to reasons motivated by feelings for their partners, financial support for their children, the miserable life in which they find themselves, the “feminization of poverty”, “for the love of the child”. In this study, the State assumes an anthropomorphic configuration. The etnografy documents and the interviews carried out with police officers reveal that the woman is arrested by an “unexpected”, still has an 'arrest in flagrante delicto' extended to that of her partner. The verb to keep is, to a large extent, the prison of the woman. The family's social visit was consolidated as the greatest form of humanization of punishment. Affections are the becomings, potentialities of existing of the prisoner and his family. The Covid-19 pandemic consolidates the legitimacy of old practices of the prison system, systematizes the obstacle of affections through the prohibition of visits. Ethnographic data point to obstacles to the experience of the prisoner's and her family's affections as the rationality of the prison system in the construction and imputation of pain. The woman's imprisonment is seen as more bearable than the man's imprisonment due to motherhood. The rupture of the family visit constitutes a fact present in all times in prison, being observed, from this particular constellation, as a macro-social data. Obstacles to family visits cause physical and psychological health problems for women and children. The pain and idleness of the prisoners constitute the rationality of the prison system. The violent practices of the body search are seen as a sanction that goes beyond the dosimetry of the penalty that extends to the family, going beyond the person of the convict. Self-mutilation, a characteristic imbricated in the female prison, consists in the production of life. The methodological resources used in the research were direct observation, field notebook, informal conversations, interviews, drawings, memorization, ethnographies of court sentences in the only Drug Court in the city of João Pessoa-PB.